PENGARUH KEGIATAN MUTHALA’AH TERHADAP KEMAMPUAN MEMBACA KITAB KUNING DI KELAS VI MTI TARUSAN KAMANG MUDIAK - Marisa; Supriadi; Nurhasnah; Khairuddin (CV. ADIBA AISHA AMIRA, 2024)
This research is motivated by the reality in the field is that during the process of reading the Kunung book In progress, researchers saw that students were not reading the Yellow Book and I still have trouble reading the yellow book. Based on the problem Finding out how much of an impact Muthalaah Night Activities have on sixth graders' Yellow Book reading comprehension is the driving force for this study. Researchers employed experimental research methods in this study. A quasi-experimental design is derived from this experimental research. Comprehensive planning A posttest alone control design was utilised in this investigation. According to the findings from the examination of the ability to read the yellow book students during the reading process by implementing Muthala’ah activities Evening. In the process of reading, students are seen paying attention and listen to the explanation given by the researcher carefully, Students also actively ask questions if there is material they do not understand. Besides Meanwhile, the students also looked enthusiastic when studying in groups and students looks active during the discussion by collaborating with group and share their opinions with each other. After data collection is carried out, it is then processed and carried out examine the hypotheses with the t-test. Assuming α = 0.05 as the level of significance. Criteria for testing: If tcount is greater than or equal to ttable, accept Ha; otherwise, reject H0. A t-test for evaluating hypotheses reveals that the computed t-value (0.4438) is larger than ttable. Therefore, we agree H1, which states that Muthala’ah Activities have an effect. Concerning Class VI MTI Students' Capacity to Read the Yellow Book Karen Kamang Mudiak's Tarusan.